2010
DOI: 10.1073/pnas.1007613107
|View full text |Cite
|
Sign up to set email alerts
|

Robust circadian clocks from coupled protein-modification and transcription–translation cycles

Abstract: The cyanobacterium Synechococcus elongatus uses both a protein phosphorylation cycle and a transcription-translation cycle to generate circadian rhythms that are highly robust against biochemical noise. We use stochastic simulations to analyze how these cycles interact to generate stable rhythms in growing, dividing cells. We find that a protein phosphorylation cycle by itself is robust when protein turnover is low. For high decay or dilution rates (and compensating synthesis rates), however, the phosphorylati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 55 publications
(137 reference statements)
4
105
0
Order By: Relevance
“…Moreover, experiments in which kaiBC was placed under the control of an exogenous promoter in order to eliminate the TTFL showed that, under conditions that favor rapid growth, enhanced variations in phase are observed among individual cells within the population (61). These data, coupled with mathematical modeling, suggest that the TTFL is required for the generation of robust circadian oscillations specifically under conditions of rapid growth (61,62). In contrast to what is observed in eukaryotic systems, the phasing of the cyanobacterial clock is inherited from mother cell to daughter cell with negligible intercellular coupling (63,64).…”
Section: Regulation Of the Kai-based Oscillatormentioning
confidence: 92%
“…Moreover, experiments in which kaiBC was placed under the control of an exogenous promoter in order to eliminate the TTFL showed that, under conditions that favor rapid growth, enhanced variations in phase are observed among individual cells within the population (61). These data, coupled with mathematical modeling, suggest that the TTFL is required for the generation of robust circadian oscillations specifically under conditions of rapid growth (61,62). In contrast to what is observed in eukaryotic systems, the phasing of the cyanobacterial clock is inherited from mother cell to daughter cell with negligible intercellular coupling (63,64).…”
Section: Regulation Of the Kai-based Oscillatormentioning
confidence: 92%
“…Studies of circadian clocks have revealed other precedents. For example, the cyanobacterium Synechococcus possesses both a transcriptional oscillator and an enzymatic phosphorylation/ dephosphorylation oscillator that is independent of transcription; these are normally coupled, but each can generate a circadian rhythm in the absence of the other (Kitayama et al, 2008;Zwicker et al, 2010). Moreover, many organisms, from bacteria to mammals, contain a non-transcriptional oxidation/reduction circadian oscillator that operates in parallel with a transcriptional circadian oscillator (Edgar et al, 2012).…”
Section: Research Article Development 140 (2)mentioning
confidence: 99%
“…However, it has been shown to encompass a transcription/translation feedback loop in which the KaiABC genes and their products participate in positive and negative autoregulatory feedback loops (10,11), similar to what is observed in higher organisms (12). Different studies connect the KaiABC central clock with control over transcriptional activity through different effectors such as the histidine kinase Synechococcus adaptative sensor A, the putative transcription factor regulator of phycobilisome-associated A (13,14), the regulator of phycobilisome-associated B regulator (15), low amplitude and bright A, the sensor histidine kinase circadian input kinase A (16,17), and the input factors Pex and light-dependent period A.…”
mentioning
confidence: 99%